2020
DOI: 10.18553/jmcp.2020.19306
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Brexanolone Versus Selective Serotonin Reuptake Inhibitors for the Treatment of Postpartum Depression in the United States

Abstract: BACKGROUND: Brexanolone injection (BRX) was approved by the FDA in 2019 for the treatment of adult patients with postpartum depression (PPD), but its cost-effectiveness has not yet been evaluated. OBJECTIVE: To estimate the cost-effectiveness of BRX compared with treatment with selective serotonin reuptake inhibitors (SSRIs) for PPD. METHODS: We projected costs (2018 U.S. dollars) and health (qualityadjusted life-years [QALYs]) for mothers treated with BRX or SSRIs and their children. A health state transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…53 A recent cost-effectiveness analysis also indicates that treatment of adults with PPD using BRX is cost-effective compared to SSRIs over an 11-year time horizon, particularly for patients with severe symptoms, based on a United States health care payer perspective. 54 There are limitations to this study. As this analysis was conducted on clinical trial data, estimating MCT values was not an objective at study onset, therefore the estimates reported here should be validated on an external dataset, and ideally additional anchors, including patient-reported anchors, should also be included.…”
Section: Discussionmentioning
confidence: 90%
“…53 A recent cost-effectiveness analysis also indicates that treatment of adults with PPD using BRX is cost-effective compared to SSRIs over an 11-year time horizon, particularly for patients with severe symptoms, based on a United States health care payer perspective. 54 There are limitations to this study. As this analysis was conducted on clinical trial data, estimating MCT values was not an objective at study onset, therefore the estimates reported here should be validated on an external dataset, and ideally additional anchors, including patient-reported anchors, should also be included.…”
Section: Discussionmentioning
confidence: 90%
“…However, its use is currently restricted to certified healthcare facilities and must be infused over 60 hours. These factors, along with its cost of approximately $39,000 for the drug and its administration, have significantly limited its access [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The continuous infusion, the need for an inpatient facility, requiring continuous pulse oximetry monitoring, and side effects such as sedation leading to the discontinuation of this treatment all add to the challenges of brexanolone becoming a real-world practical treatment for PPD [51]. Further adding to the barriers is the total cost of USD 34,000 (USD 7450 per vial and about 4.58 vials on average), excluding the inpatient facility cost [50,51]. This makes its use as the treatment of choice cost 36 times more in contrast to mainstream therapy.…”
Section: Discussionmentioning
confidence: 99%